(untitled) (Al-Mansour Journal, 2025)
This study aims to compare the effect of ephedrine and phenylephrine on the Apgar score of newborns after cesarean section under spinal anesthesia. A comparative pilot study was conducted on 40 pregnant women selected for elective cesarean section. They were randomly assigned to two groups: one group received ephedrine Another received phenylephrine when hypotension occurred. Apgar scores were recorded at the first and fifth minutes after birth, and the data were analyzed using the Kolmogorov-Smirnov test to check the normality of the distribution, followed by the Wilcoxon Signed-Rank test to measure statistical differences. The results showed statistically significant differences between the Apgar scores at the first and fifth minutes for both drugs (p<0.05), with ephedrine having a relative advantage in the number of cases that recorded positive improvements in scores. The results indicate that the use of ephedrine contributes more clearly to improving the immediate assessment of the newborn’s condition than phenylephrine. Further studies with larger samples are recommended to monitor the long-term effects on the newborn’s health.